Human virology in Latin America : from biology to control - Ludert, Juan Ernesto; Pujol, Flor H.; Arbiza, Juan (Springer, 2017)
This book is a compilation of some of the most remarkable contributions made by scientists currently working in Latin America to the understanding of virus biology, the pathogenesis of virus-related diseases, virus epidemiology, vaccine trials and antivirals development. In addition to recognizing the many fine virologists working in Latin America, Human Virology in Latin America also discusses both the state-of-the-art research and the current challenges that are being faced in the region, in hopes of inspiring young scientists worldwide to become eminent virologists.
Includes index.
Keywords: Medical virology -- Latin America.; Latin America.; elektronické knihy; electronic books